2021
DOI: 10.3389/fphys.2021.681135
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Coronary Blood Flow by the Carotid Body Chemoreceptors in Ovine Heart Failure

Abstract: Carotid bodies (CBs) are peripheral chemoreceptors, which are primary sensors of systemic hypoxia and their activation produces respiratory, autonomic, and cardiovascular adjustments critical for body homeostasis. We have previously shown that carotid chemoreceptor stimulation increases directly recorded cardiac sympathetic nerve activity (cardiac SNA) which increases coronary blood flow (CoBF) in conscious normal sheep. Previous studies have shown that chemoreflex sensitivity is augmented in heart failure (HF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 39 publications
0
9
1
Order By: Relevance
“…We have previously shown that atropine alone does not alter CoBF in sheep where HR has been fixed with cardiac pacing. 19 During administration of atropine during exercise, no statistically significant difference was observed in any hemodynamic parameters compared to controls measured during exercise (Figure 4D through 4I).…”
Section: Inhibition Of Acetylcholine Does Not Affect Cardiac Function...mentioning
confidence: 80%
See 4 more Smart Citations
“…We have previously shown that atropine alone does not alter CoBF in sheep where HR has been fixed with cardiac pacing. 19 During administration of atropine during exercise, no statistically significant difference was observed in any hemodynamic parameters compared to controls measured during exercise (Figure 4D through 4I).…”
Section: Inhibition Of Acetylcholine Does Not Affect Cardiac Function...mentioning
confidence: 80%
“…11,14,22 In exercise physiology, much of the study on vagal control of the heart has focused on the regulation of HR alone. 19,23,24 Historically, it has been thought that since HR increases, vagal tone must be withdrawn. 25,26 While this is a simplified assessment, the technical nature of studying cardiac vagal control in humans and conscious animal models, alongside the repeated conflation that cholinergic blockade equals vagal blockade, 4,6,26,27 means that, to date, most measures of vagal tone have been indirect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations